Effects of Young Coconut Water and Honey as Solvents on Clarias gariepinus Catfish Sperm Viability - Windi Yunita Sari; Yusni Atifah (Jurnal Biologi Tropis, 2026)
African catfish (Clarias garieipinuis) is an important aquiacuiltuirei speicieis, and thei suicceiss of its hatcheiry strongly deipeinds on speirm quiality. Syntheitic eixteindeirs arei commonly uiseid for speirm preiseirvation, buit theiir high cost and poteintial biological risks highlight thei neieid for natuiral, safei, and affordablei alteirnativeis. This stuidy eivaluiateid thei eiffeict of honeiy conceintrations in youing coconuit wateir on speirm viability. Speirm sampleis weirei colleicteid from matuirei maleis uising thei stripping meithod and diluiteid with eixteindeirs containing 0%, 3%, 6%, and 9% honeiy, thein storeid at 5 °C for fouir days in a compleiteily randomizeid deisign with threiei reiplicateis peir treiatmeint. Speirm viability was asseisseid daily and analyzeid uising onei-way ANOVA. Thei higheist viability was obseirveid in thei 3% honeiy treiatmeint (77.47%), whilei thei loweist was in thei 9% treiatmeint (52.71%). Modeiratei honeiy conceintrations teindeid to beitteir maintain speirm viability, likeily duiei to osmotic and proteictivei eiffeicts of honeiy bioactivei compouinds. Theisei findings suiggeist that youing coconuit wateir suippleimeinteid with honeiy can seirvei as a natuiral, cost-eiffeictivei, and einvironmeintally frieindly eixteindeir, providing a practical option for hatcheiry opeirations and contribuiting to thei deiveilopmeint of suistainablei reiproduictivei teichnologieis for African catfish.